The Deferred Embryo Transfer Strategy Seems Not to be a Good Option After Repeated IVF/ICSI Cycle Failures. (September 2019) - Bourdon, Mathilde; Santulli, Pietro; Chen, Yulian; Patrat, Catherine; Pocate-Cheriet, Khaled; Maignien, Chloé; Marcellin, Louis; Chapron, Charles
Objective: The aim of this study was to assess whether a deferred frozen–thawed embryo transfer (Def-ET) offers any benefits compared to a fresh ET strategy in women who have had 2 or more consecutive in vitro fertilization (IVF)/intracytoplasmic injection (ICSI) cycle failures. Design: An observational cohort study in a tertiary referral care center including 416 cycles from women with a previous history of 2 or more consecutive IVF/ICSI failures cycles. Both Def-ET and fresh ET strategies were compared using univariate and multivariate logistic regression models. The main outcome measured was the cumulative live birth rate (CLBR). Results: A total of 416 cycles were included in the analysis: 197 in the fresh ET group and 219 in the Def-ET group. The CLBR was not significantly different between the fresh and Def-ET groups (58/197 [29.4%] and 57/219 [26.0%], respectively, P = .437). In addition, after the first ET, there was no significant difference in the live birth rate between the fresh ET and Def-ET groups (50/197 [25.4%] vs 44/219 [20.1%], respectively). Multivariate logistic regression analysis indicated that compared to the fresh strategy, the Def-ET strategy was not associated with a higher probability of live birth. Conclusions: In cases with 2 or more consecutive prior IVF/ICSI cycle failures, a Def-ET strategy did not result in better ART outcomes than a fresh ET strategy.